Pattern and Prevalence of Congenital Malformation of fetus- Autopsy Based Study in BTGH (Basaweshwara Teaching and General Hospital) Mahadevappa Rampure Medical College(MRMCK). Kalaburgi. From Jan 2016- Jan 2017 (Medico Legal Update, 2019)
Introduction: Autopsy is an important aspect of clinical service, providing clinicians with critical feedbackregarding diagnostic accuracy, therapeutic efficacy, and medical complication1Among the Dravidian populations of the four southern states of India, Andhra Pradesh, Karnataka, Kerala,and Tamil Nadu, consanguineous marriages are5 strongly favored which is one of the known cause ofcongenital malformation. Congenital malformation is emerging as an important component in the perinatalmortality and morbidity with considerable repercussion on the families’ affected. Early diagnosis of lifethreatening congenital malformation can pave the way for surgical correction or palliation of these infants1.Material and Method : We studied 217 cases of fetal autopsies from January 2016 to January 2017 durationof one-year retrospective study. Purpose of study is pathological and legal correlation in aspect of M: F ratio,age of termination of pregnancy, fetal anomalies & its pattern in Btgh Mrmck.Karnataka.Results: Total fetal autopsies done are 217, out of which 51 are anomalous. Among them 22 are male and28 are female babies and 1 sex is not determined {ambiguous}. In our study M: F ratio is 1:1.35. Mostcommon cause of death found in autopsy examination is meconium aspiration in male fetus and placentalinsufficiency in female fetus. And mean age of gestation is 29 week and 30 weeks resp. Mean age of themother is 29 years.Conclusion: Fetal autopsies provide us an important information about pattern of anomalies, their incidenceand cause of death in relation with sex and age of fetus, maternal age, along with socio-economic status.Legal implications regarding fetal autopsies is still a field of interest.